A linguagem escrita na perspectiva discursiva em uma escola de Paço do Lumiar/MA: o ensino por meio do texto/gênero do discurso no ensino fundamental I - SILVA, Paula Ticiane Silva da (2023)
The research entitled WRITTEN LANGUAGE IN THE DISCURSIVE PERSPECTIVE IN A SCHOOL IN PAÇO DO LUMIAR/MA: teaching through text/discourse genre in elementary school I was research developed within the scope of the professional master's degree which had the general objective of understanding how to develop the process of teaching written language from the discursive perspective of language, starting from the text/discourse genre as the basic unit of didactic organization, with a view to developing, based on a collaborative intervention, theoretical and methodological propositions that support teaching teachers fundamental I, materialized in a Portfolio. To achieve what we set out to do, we chose collaborative action research as a methodology, based on Ibiapina (2008). With the emergence of the Covid 19 Pandemic and the closure of schools at the beginning of 2020, we had to rethink the research path. Therefore, we chose to generate data using instruments such as: pedagogical meetings, narrative interviews and questionnaire application. To help us with the theoretical foundation on this path, it was necessary to seek theoretical support from Geraldi (2001), Bajard (2007, 2012, 2014), Ferrarezi Júnior and Carvalho (2015), Goulart (2020), Jolibert (1994), Smolka (1993 , 2003, 2012), Frade (2007), Soares (2003), Bakhtin (2000), which address the conceptions of language and the discursive and dialogic process during the process of appropriating reading and writing. After developing the diagnosis through narrative interviews and pedagogical meetings, we noticed weaknesses in the teachers' knowledge regarding the discursive perspective and its application in the classroom, in addition to the desire to get closer to this theoretical contribution. The research results were aimed at responding to the diagnosis, and due to the consequences caused by the Covid-19 pandemic, the redirection of the path led us only to the elaboration of methodological propositions materialized in the research product, the Portfolio of Didactic Clues that aims to encourage teachers in the search for greater knowledge about the process of appropriation of written language by children in elementary school I from the perspective defended by us, that is, without carrying out a direct intervention in the classrooms of school researched. Thus, we conclude that diving into research was extremely relevant for the field of methodological knowledge aimed at the teachers involved in the research, for the Researcher, as well as for all Teachers who have access to the material produced.